Cpn60.1 (GroEL1) Contributes to Mycobacterial Crabtree Effect: Implications for Biofilm Formation - Zeng, Sheng (Front Microbiol, 2019)
Biofilm formation is a survival strategy for microorganisms facing a hostile environment. Under biofilm, bacteria are better protected against antibacterial drugs and the immune response, increasing treatment difficulty, as persistent populations recalcitrant to chemotherapy are promoted. Deciphering mechanisms leading to biofilms could, thus, be beneficial to obtain new antibacterial drug candidates. Here, we show that mycobacterial biofilm formation is linked to excess glycerol adaptation and the concomitant establishment of the Crabtree effect. This effect is characterized by respiratory reprogramming, ATP downregulation, and secretion of various metabolites including pyruvate, acetate, succinate, and glutamate. Interestingly, the Crabtree effect was abnormal in a mycobacterial strain deficient for Cpn60.1 (GroEL1). Indeed, this mutant strain had a compromised ability to downregulate ATP and secreted more pyruvate, acetate, succinate, and glutamate in the culture medium. Importantly, the mutant strain had higher intracellular pyruvate and produced more toxic methylglyoxal, suggesting a glycolytic stress leading to growth stasis and consequently biofilm failure. This study demonstrates, for the first time, the link between mycobacterial biofilm formation and the Crabtree effect.